1989
DOI: 10.1002/pssb.2221540134
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Mössbauer and Semiconductor Parameters of Tin Telluride

Abstract: The observed correlation between the llsSn Mossbauer isomer shift 6 and the hole concentration in tin telluride is explained on the basis of the latest literature data on the peculiarities of the band structure. It is evaluated that the temperature change from 40 to 400 K should not influence the isomer shift. Tennypaga oxoBa AaHo 06mCHeHIle ~a 6 n m~a e~o t HoppenRqm Memay llgSn ~ecc6ay-Ha OCHOBe HOBelkIEiX JIHTepaTypHbIX gaHHb1X 06 OCO6eHHOCTRX 30HHOg CTPYHTYPbI BPOBCKUM H30MePHbIM CABEirOM 6 Ei KOHqeHTpaIJH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Indeed, experimental values of G for undoped Pb 1--x Sn x Te crystals determined in this work are equal to G = (0.75 AE 0.03) and (0.80 AE 0.03) mm/s for x = 0.2 and 0.3, respectively. According to the data presented in [11], G = (0.84 AE 0.03) mm/s for SnTe which had been synthesized and annealed at the temperature equal to 0.7 T liq for a long time. The linewidth of the unannealed SnTe sample is equal to G = (0.90 AE 0.05) mm/s [12].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, experimental values of G for undoped Pb 1--x Sn x Te crystals determined in this work are equal to G = (0.75 AE 0.03) and (0.80 AE 0.03) mm/s for x = 0.2 and 0.3, respectively. According to the data presented in [11], G = (0.84 AE 0.03) mm/s for SnTe which had been synthesized and annealed at the temperature equal to 0.7 T liq for a long time. The linewidth of the unannealed SnTe sample is equal to G = (0.90 AE 0.05) mm/s [12].…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the Te content in nondoped SnTe leads to a monotonous growth of the hole concentration p H , because vacancies act as acceptors [9,10]. The fact that increasing Te content at a fixed In concentration results initially in a drop of p H (i.e., growth of R H ) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although 5s-electrons make the main contribution to the isomer shift, it is known that 5p-electrons of tin play a primary role in the chemical bond in SnTe [11]. It has been shown that a correlation exists between changes in the charge carrier concentrations and isomer shifts both in the undoped Sn-Te and doped systems, and that an increase in the hole concentration correlates with a decrease in the isomer shift [10]. This correlation could be explained in the following way.…”
Section: Discussionmentioning
confidence: 99%